2004
DOI: 10.1021/jm030448l
|View full text |Cite
|
Sign up to set email alerts
|

Punaglandins, Chlorinated Prostaglandins, Function as Potent Michael Receptors To Inhibit Ubiquitin Isopeptidase Activity

Abstract: Cyclopentenone prostaglandins exhibit unique antineoplastic activity and are potent growth inhibitors in a variety of cultured cells. Recently the dienone prostaglandin, Delta(12)-PGJ(2), was shown to preferentially inhibit ubiquitin isopeptidase activity of the proteasome pathway. It is theorized that isopeptidase inhibition and general cytotoxicity of prostaglandins depend on olefin-ketone conjugation, electrophilic accessibility, and the nucleophilic reactivity of the endocyclic beta-carbon. Delta(12)-PGJ(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
67
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 31 publications
4
67
0
Order By: Relevance
“…Hence, it should not be surprising that also F6 and G5 act as inhibitors of the ubiquitin-proteasome system. As a matter of fact, the presence of a pharmacophore that confers inhibitory activity toward ubiquitin isopeptidases (12,(14)(15)(16) and experimental data here reported has confirmed that these new compounds can impede ubiquitin-dependent protein degradation.…”
Section: Discussionsupporting
confidence: 66%
“…Hence, it should not be surprising that also F6 and G5 act as inhibitors of the ubiquitin-proteasome system. As a matter of fact, the presence of a pharmacophore that confers inhibitory activity toward ubiquitin isopeptidases (12,(14)(15)(16) and experimental data here reported has confirmed that these new compounds can impede ubiquitin-dependent protein degradation.…”
Section: Discussionsupporting
confidence: 66%
“…1A). A similar pharmacophore was previously described in the pan-DUB inhibitor prostaglandin lipid derivatives, which function as potent Michael receptors to inhibit the activities of DUBs [28,29]. The alpha, beta-unsaturated carbonyl center in the cyclopentenone ring of prostaglandins could react with the DUB catalytic cysteine thiol group, resulting in a covalent adduct [30].…”
Section: Discussionmentioning
confidence: 79%
“…In fact, cross-conjugated dienone prostaglandins are observed to undergo reversible conjugate additions. 18,19 While it is appreciated that the use of conjugate additions can produce tight binding ligands, there has been a reluctance to install such reactive functionality in drug candidate molecules owing to potential poor bioavailability and increased toxicity. The destruction of protein-reactive therapeutics through non-selective addition to scavenger nucleophiles, such as glutathione, would be expected to seriously jeopardize the bioavailability of the therapeutic.…”
mentioning
confidence: 99%